Local ownership of health policy and systems research in low-income and middle-income countries: a missing element in the uptake debate. Issue 4 (28th August 2019) - Vanyoro, Kudakwashe Paul; Hawkins, Kate; Greenall, Matthew; Parry, Helen; Keeru, Lynda
Abstract : Health policy and systems researchers (HPSRs) in low-income and middle-income countries (LMICs) aim to influence health systems planning, costing, policy and implementation. Yet, there is still much that we do not know about the types of health systems evidence that are most compelling and impactful to policymakers and community groups, the factors that facilitate the research to decision-making process and the real-world challenges faced when translating research findings into practice in different contexts. Drawing on an analysis of HPSR from LMICs presented at the Fifth Global Symposium on Health Systems Research (HSR 2018), we argue that while there is a recognition in policy studies more broadly about the role of co-production, collective ownership and the value of localised HPSR in the evidence-to-policy discussion, 'ownership' of research at country level is a research uptake catalyst that needs to be further emphasised, particularly in the HPSR context. We consider embedded research, participatory or community-initiated research and emergent/responsive research processes, all of which are 'owned' by policymakers, healthcare practitioners/managers or community members. We embrace the view that ownership of HPSR by people directly affected by health problems connects research and decision-making in a tangible way, creating pathways to impact.